2010
DOI: 10.1177/008124631004000208
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Big Five Personality Traits and Burnout in South African University Students

Abstract: Research on burnout has tended to explore the organisational factors associated with this condition. However, an important factor that is often overlooked is the relationship between burnout and personality. We explored this relationship in South African university students. The participants completed the Basic Traits Inventory — Short, the Maslach Burnout Inventory — Student Survey and a biographical questionnaire. The results revealed several significant relationships between personality traits and burnout w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 46 publications
1
37
0
10
Order By: Relevance
“…In South Africa a few studies have been done on student burnout and student engagement (Gauché, 2006;Grobbelaar, Malan, Steyn & Ellis, 2010;Grobbelaar, Malan, Steyn & Ellis, 2011;Morgan & De Bruin, 2010;Mostert, Pienaar, Gauché & Jackson, 2007;Pienaar & Sieberhagen, 2005;Strydom, Kuh & Mentz, 2010). However, none of these studies focused on core self-eval uation traits (self-esteem and self-efficacy), career decision-making difficulties or social support as predic tors of student burnout and engagement.…”
Section: Study Contextmentioning
confidence: 99%
“…In South Africa a few studies have been done on student burnout and student engagement (Gauché, 2006;Grobbelaar, Malan, Steyn & Ellis, 2010;Grobbelaar, Malan, Steyn & Ellis, 2011;Morgan & De Bruin, 2010;Mostert, Pienaar, Gauché & Jackson, 2007;Pienaar & Sieberhagen, 2005;Strydom, Kuh & Mentz, 2010). However, none of these studies focused on core self-eval uation traits (self-esteem and self-efficacy), career decision-making difficulties or social support as predic tors of student burnout and engagement.…”
Section: Study Contextmentioning
confidence: 99%
“…Schaufeli et al have developed a student version of the Maslach Burnout Inventory (MBI-SS) (Schaufeli et al 2002). Many studies have used this scale to examine student's burnout levels (Esteve, 2003;Breso et al, 2010;Gan and Shang, 2007;Hu and Schaufeli, 2009;Jia et al, 2009;Lee et al 2010;Lingard, 2007;Morgan, B., 2008;Zhang et al 2007;Salanova et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that self-efficacy (Fives et al, 2007;Yang, 2004;Yang and Farn, 2005) and social support (Gündüz et al, 2012;Yang, 2004;Yang and Farn, 2005) are significant variables that predict less burnout among students, indicating the more social support they receive and the more they feel selfefficacious the less burnout they have. Particular demographic characteristics of students were also related to school burnout (Morgan and De Bruin, 2010). For Dündar 111…”
Section: Burnout Among College Students and Associated Factorsmentioning
confidence: 99%
“…academic workload, exams,adjustment to school environment, career concerns, etc. (Mehdinezhad, 2011;Morgan and De Bruin, 2010). Studies have revealed that self-efficacy (Fives et al, 2007;Yang, 2004;Yang and Farn, 2005) and social support (Gündüz et al, 2012;Yang, 2004;Yang and Farn, 2005) are significant variables that predict less burnout among students, indicating the more social support they receive and the more they feel selfefficacious the less burnout they have.…”
Section: Burnout Among College Students and Associated Factorsmentioning
confidence: 99%